Personality of semen donors and their social behaviour - Taus, L; Gerzová, J (Czechoslovak medicine, 1991)
The authors examined, using three generally accepted methods, the personality structure of 80 semen donors (Cattell's 16-factor questionnaire, 16PF, Eysenck's personality questionnaire, EOD, and Leary's method of interpersonal diagnosis of personality). The donors were selected by means of the Questionnaire of semen donors. The group is subdivided into four sub-groups by the grade of education, i.e. university graduates, men with secondary and elementary education and university students. All are 20-40 years old. The authors describe the assembled results in different sub-groups and in the group as a whole and compare them mutually and with the standardized norm. With regard to the specificity of individual methods and their application the findings are summarized. The donors are balanced personalities, slightly extrovert, emotionally well developed with a realistic outlook. They have positive, sensitive relations with their environment an behaviour towards other people, they are considerate, careful and disciplined. They respect social norms as regards preservation of originality of personality. They have a slight tendency of sheltering behaviour, they wish to be somewhat more aggressive. No pathological phenomena were observed in the donors. Their intelligence is above average. They make a favourable impression with regard to the demand of mental health and transmission of genetic information. The authors evaluate favourably the Questionnaire for semen donors as the method for selection of donors.
Keywords: stupeň vzdělání; Social Behavior; Personality; sociální chování; Adult; Insemination, Artificial, Heterologous; Male; lidé; dospělí; mužské pohlaví; osobnost; Educational Status; Humans; heterologní inseminace